If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + -4 = 8y + -8 Reorder the terms: -4 + 9y = 8y + -8 Reorder the terms: -4 + 9y = -8 + 8y Solving -4 + 9y = -8 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. -4 + 9y + -8y = -8 + 8y + -8y Combine like terms: 9y + -8y = 1y -4 + 1y = -8 + 8y + -8y Combine like terms: 8y + -8y = 0 -4 + 1y = -8 + 0 -4 + 1y = -8 Add '4' to each side of the equation. -4 + 4 + 1y = -8 + 4 Combine like terms: -4 + 4 = 0 0 + 1y = -8 + 4 1y = -8 + 4 Combine like terms: -8 + 4 = -4 1y = -4 Divide each side by '1'. y = -4 Simplifying y = -4
| 0.08a=72 | | 4t^3-4=0 | | 17-4(3)+4= | | 25a=-3+3a | | 5[8+5(4-2)]= | | (9/z)-(2/z)=21 | | 35000=x-.06x-.0022x-1000-96000 | | 35000=x-.06x-.0022x-1000 | | 3/10a=6 | | 12=r/3 | | 16-2(2)+2= | | 143x^2-1440x+3600=0 | | 176=-4 | | -4-(-2)+5-3= | | 3[4+6(6-3)]= | | -5(3t-4)+4t=7T-3 | | x/3=x/5+3 | | 5x^4+23x^2-42=0 | | k/5+3=6/5 | | log(8)+log(x+9)=log(128) | | 3(x+3)-5=5x-2(-4+x) | | 9x^2-3x+9=0 | | y=3+3sin(3x-7) | | 3m^2-3m-5=0 | | 20=-2/3x | | 0.12(y-5)+0.18y=0.20y-0.03(30) | | 9y=1/5 | | 2a+5a+18=0 | | 0.08(y-8)+0.06y=0.12y-0.01(50) | | 0.14(y-2)+0.16y=0.02y-0.01(70) | | x-11/2=19/6 | | 0.12(y-7)+0.14y=0y-0.01(20) |